Prediksi Perubahan garis Pantai Menggunakan Program GENESIS (Studi Kasus Pantai Kelapa Rapat) - Ahmad Zakaria; . Sumiharni; Arya Jaya Sumbahan (UNIVERSITAS LAMPUNG, 2013)
Shoreline profile has a tendency to adjust the wave effect on the shoreline. Changes to the lineconsists of two kinds of erosion and sedimentation. Waves that can affect shorlines rise due to theinfluence of the wind, the wind blowing duration and distance without hurdles when the windblows (fetch). The waves were coming to cause the migration of sediment on the shoreline. Ifwaves erode sediment on the shoreline, shoreline will occur erosion and if the waves bring sedi-ment to the shoreline, on the shoreline sedimentation will occur. For example there is the KelapaRapat Beach (Pesawaran). On the beach, there is a highway a short distance away from theshoreline. Potential erosion will occur at the shoreline can cause breakdown of the resulting ero-sion of sediment on the shoreline. Due to the potential, then do research using GENESIS programto be able to estimate the extent of erosion potential disruption accessibility having an effect waycontained in about Kelapa Rapat Beach.